Layered atomic structures of double oxides for low shear strength at high temperatures - Stone, D.; Liu, J.; Singh, D.P.; Muratore, C.; Voevodin, A.A.; Mishra, S.; Rebholz, C.; Ge, Q.; Aouadi, S.M. (Scripta materialia, 2010)
Double oxide phases combining a transition metal and a noble metal have recently become a subject of investigation as solid lubricant materials for high-temperature tribological applications. Here, we study the changes in chemistry and crystal structure of silver molybdate (Ag 2Mo 2O 7) and silver tungstate (Ag 2WO 4) thin films and powders from 25 to 600 °C. We show, using ab initio molecular dynamics, high-temperature X-ray diffraction, high-temperature Raman spectroscopy and differential scanning calorimetry in combination with sliding tests, that the layered atomic structure of silver molybdate facilitates sliding, resulting in a low coefficient of friction (<0.2) from 300 to 500 °C.